Development And Characterization Of The Ionic Polymer Metal Composite Actuated Contractile Water Jet Thruster - Shaari, Muhammad Farid (2017)
Ionic Polymer Metal Composite (IPMC) is a type of smart material that can be utilized as the actuator for contractile water jet thruster (CWJT) which is an alternative thruster for autonomous underwater vehicle (AUV). The advantages of IPMC actuator are light, flexible, able to be utilized underwater and consuming low voltage. However, IPMC low actuation force has limited the thrust generation. Hence, this research had been conducted to investigate the character of the fluid flow generated by the IPMC actuation on the CWJT. This investigation includes the observation on the relation of few factors that influence the thrust generation such as the nozzle aperture size, supply voltage for IPMC actuation and actuation frequency. This research consists of designing the conceptual prototype thruster, fabricating and characterizing the IPMC actuator, simulating the fluid flow of the prototype design and few experiments for data validation. The results and validation from the experiments showed that nozzle aperture size and actuation frequency of the IPMC actuator were influential factors in the development of IPMC actuated CWJT. The feasible actuation frequency was 0.1 Hz. Any higher frequency than 0.1 Hz would decline the CWJT contraction performance. The maximum thrust achieved in this research was 4.52 mN at 6 V supply. It is not feasible for heavy and more than 1 m long AUV. However, it suits for small or micro AUV that works in low current waters.